Caracterização soroepidemiológica da infecção por vírus Maedi-Visna e Brucella ovis em ovinos no Estado de Minas Gerais - Ana Paula Ribeiro Marques (2006)
The prevalence of the infection by Maedi-Visna lentivirus (MVV) and Brucella ovis was determine and characterized epidemiologic serum proprieties with sheep flock distributed in nine regional areas (Campo das Vertentes, Central Mineira, Metropolitana de Belo Horizonte, Noroeste de Minas, Oeste de Minas, Sul/Sudeste de Minas, Triângulo/Alto Paranaíba, Vale do Rio Doce and Zona da Mata) of 12 regional areas of Minas Gerais state. The samples were gather in 2002 and in every propriety was applied one detail questionnaire. 833 ovine serum samples was test through the agar gel imunodifusion technique. The prevalence of ovine seropositive that was found 7,9% for MVV and 5,3% for B. ovis. The percentage of positive proprieties was of 26,6% for MVV and 29,4% for B. ovis, in Minas Gerais. The positive and negative proprieties for MVV and B. ovis was classify in low, medium and high technology level. By the statistic analysis multiple logistic regression and STATA 8.0 specific program was demonstrated that technology level of the propriety and purchase of reproducers are risk factors to proprieties be positives for MVV